2022
DOI: 10.3390/ijerph19074218
|View full text |Cite
|
Sign up to set email alerts
|

Improved Water and Waste Management Practices Reduce Diarrhea Risk in Children under Age Five in Rural Tanzania: A Community-Based, Cross-Sectional Analysis

Abstract: Diarrhea remains a significant cause of morbidity and mortality among children in developing countries. Water, sanitation, and hygiene practices (WASH) have demonstrated improved diarrhea-related outcomes but may have limited implementation in certain communities. This study analyzes the adoption and effect of WASH-based practices on diarrhea in children under age five in the rural Busiya chiefdom in northwestern Tanzania. In a cross-sectional analysis spanning July-September 2019, 779 households representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…This study revealed that improved sanitation was associated with a 16% reduction in the risk of diarrhea occurrence among under-five children after matching control and treated children. This finding is in agreement with other studies conducted elsewhere [ 17 , 18 , 21 , 22 , 24 , 27 , 28 , 40 ]. A systematic and meta-analysis conducted by Wolf J et al found that improved sanitation interventions can reduce the occurrence of diarrheal diseases by 24% among children in LMICs [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This study revealed that improved sanitation was associated with a 16% reduction in the risk of diarrhea occurrence among under-five children after matching control and treated children. This finding is in agreement with other studies conducted elsewhere [ 17 , 18 , 21 , 22 , 24 , 27 , 28 , 40 ]. A systematic and meta-analysis conducted by Wolf J et al found that improved sanitation interventions can reduce the occurrence of diarrheal diseases by 24% among children in LMICs [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…A study conducted in rural Ethiopia reported that children from households who had no access to toilet facilities were 1.50 to 4.8 times more likely to having of diarrhea compared to children from households who had access to toilet facilities [ 18 , 24 , 27 , 40 ]. Also, a study conducted in rural Tanzania revealed that improved waste management reduced diarrhea risk by 63% among children [ 28 ]. However, previous studies were largely observational and used conventional regression models to investigate the association between access to improved sanitation and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These deficiencies unfortunately have serious health consequences such as deaths due to diarrhea caused by the consumption of unsafe water; and economic consequences due to the lack of access to water and sanitation. (Fuente et al, 2020;McClelland et al, 2022). The treatment of raw water before consumption is essential for the preservation of the health and the wellbeing of the populations (Sharma and Bhattacharya, 2017).…”
Section: Open Accessmentioning
confidence: 99%
“…Members of the community indicated that malaria mosquitoes breed in poorly designed toilets and septic tanks, and they strongly advocated for better toilets to control them. While improved toilets are important for preventing waterborne diseases like cholera [ 64 ], it is often non-malaria transmitting mosquitoes, such as Culex quinquefasciatus , that prefer breeding and resting in toilets [ 65 , 66 ]. The misconception that malaria-transmitting mosquitoes breed in toilets clearly highlight continued community’s engagement coupled with education on malariology.…”
Section: Discussionmentioning
confidence: 99%